“Do our children speak like we speak?” A qualitative study on Chinese American parents’ perspectives and practices regarding early literacy development and home literacy environment in infants and toddlers - Liu, Yanhui; Zou, Xuecheng; Li, Yifan; Helfrich, Sara; Chen, Feifei; Sulaimani, Mona F. (Frontiers in Education, 2025)
This study employed a qualitative thematic analysis approach to investigate Chinese-American parents’ perspectives on early literacy development (ELD) in infants/toddlers and their home literacy environments (HLE), as well as how these environments influence emergent literacy skills. Data collection involved in-depth interviews with 12 Chinese parents residing in the United States. Findings reveal that HLE significantly shapes ELD, underscoring the critical importance of primary caregivers’ home-based engagement. The study highlights the significance of immigrant/bilingual family contexts for ELD, examining how diverse approaches to implementing bilingual or English-monolingual literacy practices within immigrant households yield differential effects. Crucially, variations in parental impact beliefs and sociolinguistic perspectives were found to shape distinct pathways of emergent literacy development in infants and toddlers. This study holds important implications for both practitioners and researchers in the field of literacy development and education. Also, it supports the use of a bilingual home environment, particularly for Chinese American families, as strategies to promote infants’ ELD.